The effect of customer satisfaction, customer experience, and e-service quality on customer trust - Susanto, Desryo Adi (Universitas Ahmad Dahlan, 2024)
Purpose- Along with information and communication technology development, the business world has also developed with e-commerce services. One of the well-known e-commerce services is Shopee, which makes it easy for consumers to shop online. Consumer trust is important in e-commerce services because interactions occur through electronic devices. Consumer satisfaction, consumer experience, and quality of electronic service are some of the factors that influence consumer trust. This study aims to determine the effect of customer satisfaction, consumer experience, and e-service quality on consumer trust. Design/Methodology/Approach- This research is quantitative. The sampling method used is nonprobability sampling with a purposive sampling technique. The sample used was 110 respondents, namely Shopee e-commerce users in Indonesia. Smart PLS is used to test validity, reliability, and regression. Findings- The results of this study indicate that customer satisfaction and consumer experience are proven to have a positive effect on consumer trust, while e-service quality is proven to have a positive but insignificant impact on consumer trust. It is hoped that Shopee can increase customer satisfaction, consumer experience, and e-service quality to increase consumer confidence in online shopping. Research limitations/implications- This research is limited to Shopee e-commerce users in Indonesia. In addition, this study analyzes consumer trust by considering factors such as consumer satisfaction, consumer experience, and e-service quality. Many factors influence consumer trust but have yet to be examined in this study, so it is hoped that future research can analyze other variables that have not been studied. Originality/value- This study analyzes the factors influencing consumer trust in Shopee e-commerce users in Indonesia. Previous research has not used customer satisfaction, consumer experience, and e-service quality on Shopee e-commerce users.